2022
DOI: 10.1051/0004-6361/202142899
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a vertical kinematic oscillation beyond the Radcliffe wave

Abstract: The Radcliffe wave (RW) is a recently discovered sinusoidal vertical feature of dense gas in the proximity of the Sun. In the disk plane, it is aligned with the Local Arm. However, the origin of its vertical undulation is still unknown. This study constrains the kinematics of the RW, using young stars and open clusters as tracers, and explores the possibility of this oscillation being part of a more extended vertical mode. We study the median vertical velocity trends of the young stars and clusters along with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
(61 reference statements)
1
11
1
Order By: Relevance
“…2. The Radcliffe wave shows a vertical sinusoidal undulation (Alves et al 2020), which is not expected in the density wave theory (see Thulasidharan et al 2022). 3.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…2. The Radcliffe wave shows a vertical sinusoidal undulation (Alves et al 2020), which is not expected in the density wave theory (see Thulasidharan et al 2022). 3.…”
Section: Discussionmentioning
confidence: 74%
“…If the Radcliffe wave's undulation is somehow related to gas instabilities (Fleck 2020), stellar feedback, or perturbations in the Galactic potential (Antoja et al 2018), one would expect to find more global corrugations in the dust and young stars across the Milky Way. Such structures have been investigated in OB stars (Pantaleoni González et al 2021) and signatures of varying oscillation amplitudes across stars of different ages (5-100 Myr) are present across the disk (Thulasidharan et al 2022). Global corrugations in the dust map of Lallement et al (2022) have also been found, including regions along the Orion arm in the second quadrant and in the Sagittarius-Carina arm in the first and fourth quadrants.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While Gaia provides 6D phase space information for stars with radial velocities, many works have found it advantageous to convert these quantities into 6D action-angle space coordinates (Sanders & Binney 2016;Beane et al 2018;Trick et al 2019Trick et al , 2021. Actions are conserved quantities that describe a star's motion around the Galactic center; they assume a regular, bound orbit, as well as independence of motion in each coordinate.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the vertical velocities have a periodic structure. Thulasidharan et al (2022) studied their vertical velocities using young stars and OSCs located in the circumsolar region with a radius of 3 kpc. These authors came to the conclusion that the Radcliffe wave may be part of a larger periodic process that develops in the disk of the Galaxy.…”
Section: Introductionmentioning
confidence: 99%